Hydrophobic Modified Nanosized Crosslinked Polymer Microspheres - Chen, Hailing; Zheng, Xiaoyu; Jiang, Qinzhe; Li, Xianjie (Asian Journal of Chemistry, 2014)
The properties of nanoparticles are not only dependent on their size and shape, but also are determined by surface properties. To increase shearing resistance, hydrophobic monomer is introduced to inverse microemulsion polymerization and hydrophobic-modified cross-linked polymer nanometer microspheres (Q18) were obtained. As the object of the comparative study, non-hydrophobic cross-linked polymer microspheres (Q5) were also made. The microscopic morphology, size distribution and plugging effect of Q18 and Q5 were studied. The experimental results showed that, the morphology of Q18 and Q5 are spherical with polydispersion, the hydrophobic associations come into being in aqueous solution above a particular concentration, so the particle size distribution model of Q18 deviates from double logarithmic distribution model which matches to non-hydrophobic cross-linked polymer microspheres (Q5). Q18 can enter deeper in the sand-filled pipe than Q5 to form plugging.